11 Framing equity, diversity & inclusion efforts across the continuum of medical education using IHI model for improvement. (2nd December 2020) - Simpson, Deborah
Abstract : Background: Medical education (ME) must create equitable, diverse, and inclusive (EDI) training environments for our learners, faculty, and staff and equitable care for the patients they serve. As ME leaders spanning students to CME and libraries, we are accountable for addressing structural 'isms' in all forms (eg, race, gender-identity, religion). Objectives: Our purpose is to be intentional and public in our actions to address EDI across the continuum of medical education using the IHI Model for continuous improvement. We have 3 specific objectives, one each at the micro, meso, and macro levels. Methods: Each education department leader provided their current EDI activities and focal areas for future work along with proposed measures. These interventions were then reviewed to identify actionable interventions and associated metrics across the ME continuum seeking to use existing data for longitudinal tracking when possible. The document was shared and discussed with key stakeholders with iterative revisions to develop and assure plan engagement and support. Results: Four actionable EDI education-related categories were agreed upon: (1) purpose & culture; (2) recruitment and retention; (3) curriculum and program structure; (4) evaluation and assessment (figure 1 ). Within each category 2–3 specific PDSA interventions were identified for action within the upcoming year (e.g., scripting sessions on microaggressions, inclusion of EDI items on all medical education evaluations, assessments, and QI projects) (figures 2, 3, and 4 ). Support has been strong and widespread across all medical education stakeholders with PDSA implementation cycles already initiated including metrics tracking. Conclusions: As medical educators, it is imperative that we work to address individual and structural EDI 'isms' that limit the potential of our trainees, faculty, programs and ultimately the care of our patients. Aggregating actions using IHI model for improvement across medical education creates opportunity for synergies and impact beyond what any individual department (UME, GME, CME) can do alone.